The effect of combined training on serum concentrations of inflammatory cytokines and factors associated with metabolic syndrome in elderly women with fatty liver - Masoumeh Norouzpour; Seyed Mohammad Marandi; Mohsen Ghanbarzadeh; Abbas Ali Zare Mayavan (Shahid Beheshti University, 2022)
Purpose: Non-alcoholic fatty liver disease (NAFLD) is strongly associated with altered levels of inflammatory cytokines and increased metabolic abnormalities. In this study, the effect of combined training on serum concentrations of proinflammatory cytokines interleukin 18 (IL18), anti-inflammatory interleukin 10 (IL10) and metabolic syndrome-related factors in elderly women with fatty liver was investigated.Methods: twenty-four elderly women with NAFLD were selected purposively and were randomly divided into training (n = 12) and control (n = 12) groups. Combined training was performed for ten weeks. Using ZellBio kit, IL18 and IL10 levels were measured by ELISA and fatty liver levels by ultrasound procedure. Blood and anthropometric factors were measured as well. Statistical analysis was performed using paired samples t-test and Wilcoxon, covariance and Spearman correlation procedures.Results: Decreased and increased serum concentrations of interleukin 18 (P = 0.00) and interleukin 10 (P = 0.00) were observed in the training group compared to the control group, respectively. Also, weight, waist circumference (P = 0.00) and metabolic markers including triglyceride (TG) (P = 0.00), insulin resistance index (HOMA-IR) (P = 0.01), liver fat (P = 0.00), aspartate aminotransferase (AST) (P = 0.04) and glucose (P = 0.00) levels were significantly reduced. Moreover, there was no significant difference between insulin (P = 0.11) and alanine aminotransferase (ALT) (P = 0.07) levels.Conclusion: Combined training can improve the levels of inflammatory cytokines and reduce metabolic risk factors associated with non-alcoholic fatty liver and play an effective role in the health of the elderly by augmenting anti-inflammatory effects.